Relationships between closure operations and choice functions - equivalent descriptions of a family of functional dependencies - Vu, Nghia D. (Acta Cybernetica, 2004)
The family of functional dependencies plays an important role in the relational database. The main goal of this paper is to investigate closure operations and choice functions. They are equivalent descriptions of family of functional dependencies. The main properties of and relationship between closure operations and choice functions are presented in this paper.